Fatty acid distribution and polymorphism in solid lipid particles of milkfat and long chain omega-3 fatty acids. (1st July 2022) - Nosratpour, Mitra; Kochan, Kamila; Ma, Jisheng; Wang, Yong; Wood, Bayden R.; Haritos, Victoria S.; Selomulya, Cordelia
Highlights: Fatty acid distribution is not uniform in fish oil/milkfat solid lipid particles. Saturated fatty acids cover the outermost layer of lipid particles. Better stability with higher milkfat due to transformation to β ' during storage. Raman spectroscopy can monitor fatty acids distribution in lipid particles. Polymorphism in lipid particles is inevitable even with low storage temperatures. Abstract: Saturated fatty acid-containing lipids, such as milkfat, may protect long chain polyunsaturated fatty acids in fish oil when blended together into solid lipid particles (SLPs). One of the main challenges of SLPs is structural polymorphism, which can lead to expulsion of the protected component during prolonged storage. To investigate this phenomenon, the change in thermal and crystalline behaviours, and fatty acid distribution, were analysed in SLPs of fish oil and milkfat during storage at different temperatures for up to 28 days. X-ray diffraction analysis showed changes in molten and crystalline states occurred even at –22 °C. Room temperature (21 °C) storage led to more than 45% molten state but SLPs retained their initial shape. Confocal Raman Spectroscopy of the SLPs showed the distribution of fatty acids was not uniform, with 10 μm outermost layer of predominantly saturated fatty acids likely responsible for the intact SLP shape and stability of the core.